The Extract Welch Starfruit Leaves of Water Levels, Proteins and Fats Skipjack (Katsuwonus Pelamis ) Smoke - Ida Astuti; Asniati Ningsih (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2019)
Some food ingredients are needed by living things because they contain food substances needed in growth. This substance is commonly called the nutrient content of the food. This substance is very important, especially in metabolic processes such as breaking protein into amino acids needed for the growth of babies, children, and also helps maintain the function of carbohydrates as an energy source. The purpose of this study was to determine the effect of extracts on nutrient levels of skipjack (Katsu wonu spelamis) fufu (smoke). This study used a completely randomized design, with two treatments (the use of preservatives and without preservatives) with 3 replications. Based on the results of the study it was found that the extract of the welch starfruit leaves did not significantly affect the protein and fat content but significantly affected the water content.